Coupling Response of Piezoelectric Semiconductor Composite Fiber under Local Temperature Change - Chengcheng Liu; Wenjun Wang (Crystals, 2024)
This paper details the thermal–mechanical–electrical response of a piezoelectric semiconductor (PS) composite fiber composed of a PS layer and two piezoelectric layers under local temperature change. The phenomenological theory of thermal piezoelectric semiconductors (PSs) is adopted to obtain the analytical solution for each field in the composite fiber under local temperature change. Our findings reveal that such temperature fluctuations induce local polarization, leading to the formation of local potential barriers and potential wells that effectively impede the flow of low-energy electrons along the fiber. Furthermore, the initial carrier concentration and geometric parameters of the composite fiber exert significant influence on its individual fields. The results contribute to the structural design and practical application of piezoelectric semiconductor devices.